2015
DOI: 10.2118/168960-pa
|View full text |Cite
|
Sign up to set email alerts
|

On the Advection-Upstream-Splitting-Method Hybrid Scheme: A Simple Transient-Flow Model for Managed-Pressure-Drilling and Underbalanced-Drilling Applications

Abstract: Summary Transient flow models play an important role in the planning and follow-up of advanced well operations such as managed pressure drilling (MPD) and underbalanced operations. The most recent trend is a situation whereby flow models and control-engineering algorithms are combined in various settings to control flow parameters. This requires robust flow models and an in-depth understanding of uncertainties in the modeling process. This paper presents a simple and robust transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 13 publications
0
13
0
2
Order By: Relevance
“…The well geometry is depicted on the right square using data from Table 1 These surface data are usually observed and controlled at drilling floor. At the same time, the predicted hydraulics is validated against numerical data gotten from [5]. For the case of transient pressures, the right boundary states that circulating mud is returned out of annulus at atmospheric condition.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The well geometry is depicted on the right square using data from Table 1 These surface data are usually observed and controlled at drilling floor. At the same time, the predicted hydraulics is validated against numerical data gotten from [5]. For the case of transient pressures, the right boundary states that circulating mud is returned out of annulus at atmospheric condition.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Some emerging transient models are unfortunately characterized by high-priced computing budget and complexity [2], [3] and [4]. For instance, the paper [5] is a very interesting paper because it clarifies that transient emerging models have potential applications to fully simulate underbalanced operations. Also, it deeply discusses how efficiency and accuracy are improved by the combination of numerical schemes.…”
Section: Introductionmentioning
confidence: 99%
“…A new pressure-based method was developed to address the convergence problem of the drift flux model by Wang [27]. Among the different schemes, it has been confirmed that the advection upwind splitting method (AUSM) schemes are effective solutions to the DFM in terms of their simplicity, accuracy, and robustness [28][29][30]. Not only do these schemes display accuracy in flux difference splitting (FDS) in the boundary layer, they also exhibit robustness in flux vector splitting (FVS) when capturing strong discontinuity.…”
Section: Introductionmentioning
confidence: 99%
“…Trata-se de uma a metodologia robusta e simples de ser implementada, que vem sendo utilizada para modelar problemas de escoamento bifásico em poços em cenários de perfuração, tanto para simular situações de controle de poço convencionais quanto com a presença do MPD usada em modelos computacionais [10], [17], [33], [42].…”
Section: Método Numérico Ausmv (Advection Upstream Spliting Method)unclassified
“…Seguindo o trabalho apresentado em [17], será adotada nesta dissertação a velocidade máxima entre o observado a direita e a esquerda da interface.…”
Section: Método Numérico Ausmv (Advection Upstream Spliting Method)unclassified